Ischemic Preconditioning on Secondary Arterial and Venous Ischemia in Pedicled Axial Flaps in Wistar Rats - Rivera, Maria Jesus; Cavia-Saiz, Monica; Muñiz, Pilar; Risalde, María A.; Martínez-Delgado, Angélica (Journal of Reconstructive Microsurgery Open, 2025)
Background Microvascular complications, particularly secondary arterial and venous ischemia, pose significant challenges in reconstructive surgery. This study investigates the potential protective effects of ischemic preconditioning on flap survival, anatomopathological alterations, and immunological responses in pedicled axial flaps subjected to secondary ischemia.Methods Adult male Wistar rats underwent arterial or venous ischemia, with and without ischemic preconditioning. Histological assessments, immunohistochemistry studies, and biochemical analyses were conducted to evaluate the impact of ischemic preconditioning on inflammatory processes and tissue damage.Results Ischemic preconditioning demonstrated a statistically significant decrease in histological lesions, with reductions of 56% in arterial and 47% in venous ischemia, mainly associated with a reduction of inflammatory changes and necrosis processes. Immunological analyses revealed a significant reduction in IgM levels induced by venous ischemia, and a consistent decrease in inflammatory cytokines (interleukin-1 and tumor necrosis factor alpha) in both arterial and venous ischemia following preconditioning. Furthermore, F2-isoprostane levels indicated a lower production of oxidative stress markers in preconditioned flaps.Conclusion This study highlights the beneficial impact of ischemic preconditioning on flap viability, providing robust evidence of reduced histological lesions, inflammation, and oxidative stress in both arterial and venous secondary ischemia scenarios. These findings support the potential clinical relevance of incorporating ischemic preconditioning strategies to improve outcomes in microvascular reconstructive surgery.
Keywords: ischemic preconditioning; secondary; ischemia; arterial ischemia; venous ischemia